"Micropersonality" traits and their implications for behavioral and movement ecology research. Issue 7 (22nd February 2021) - Bailey, Joseph D.; King, Andrew J.; Codling, Edward A.; Short, Ashley M.; Johns, Gemma I.; Fürtbauer, Ines
Abstract: Many animal personality traits have implicit movement‐based definitions and can directly or indirectly influence ecological and evolutionary processes. It has therefore been proposed that animal movement studies could benefit from acknowledging and studying consistent interindividual differences (personality), and, conversely, animal personality studies could adopt a more quantitative representation of movement patterns. Using high‐resolution tracking data of three‐spined stickleback fish ( Gasterosteus aculeatus ), we examined the repeatability of four movement parameters commonly used in the analysis of discrete time series movement data (time stationary, step length, turning angle, burst frequency) and four behavioral parameters commonly used in animal personality studies (distance travelled, space use, time in free water, and time near objects). Fish showed repeatable interindividual differences in both movement and behavioral parameters when observed in a simple environment with two, three, or five shelters present. Moreover, individuals that spent less time stationary, took more direct paths, and less commonly burst travelled (movement parameters), were found to travel farther, explored more of the tank, and spent more time in open water (behavioral parameters). Our case study indicates that the two approaches—quantifying movement and behavioral parameters—are broadly equivalent, and we suggest that movement parameters can be viewed as "micropersonality" traits that give rise to broad‐scale consistent interindividual differences in behavior. This finding has implications for both personality and movement ecology research areas. For example, the study of movement parameters may provide a robust way to analyze individual personalities in species that are difficult or impossible to study using standardized behavioral assays. Abstract : We use high‐resolution tracking data of three‐spined stickleback fish ( Gasterosteus aculeatus ) to examine the repeatability of movement parameters commonly used in the analysis of discrete time series movement data and behavioral parameters commonly used in animal personality studies. We show that movement and behavioral parameters are broadly equivalent, capturing similar interindividual variation. We suggest that movement parameters can be viewed as "micropersonality" traits that give rise to broad‐scale consistent interindividual differences in behavior.